Viscoelastic covalent organic nanotube fabric via macroscopic entanglement - Koner, Kalipada; Das, Susobhan; Mohata, Shibani; Duong, Nghia Tuan; Nishiyama, Yusuke; Kandambeth, Sharath; Karak, Suvendu; Reddy, C. Malla; Banerjee, Rahul (Journal of the American Chemical Society, 2022)
Covalent organic nanotubes (CONTs) are one-dimensional porous frameworks constructed from organic building blocks via dynamic covalent chemistry. CONTs are synthesized as insoluble powder that restricts their potential applications. The judicious selection of 2,2'-bipyridine-5,5'-dicarbaldehyde and tetraaminotriptycene as building blocks for TAT-BPy CONTs has led to constructing flexible yet robust and self-standing fabric up to 3 mu m thickness. The TAT-BPy CONTs and TAT-BPy CONT fabric have been characterized by solid-state one-dimensional (1D) C-13 CP-MAS, two-dimensional (2D) C-13-H-1 correlation NMR, 2D H-1-H-1 DQ-SQ NMR, and 2D N-14-H-1 correlation NMR spectroscopy. The mechanism of fabric formation has been established by using high-resolution transmission electron microscopy and scanning electron microscopy techniques. The as-synthesized viscoelastic TAT-BPy CONT fabric exhibits high mechanical strength with a reduced modulus (E-r) of 8 (+/- 3) GPa and hardness (H) of 0.6 (+/- 0.3) GPa. Interestingly, the viscoelastic fabric shows time-dependent elastic depth recovery up to 50-70%.